Evaluation of clinical and laboratory characteristics of patients with cutaneous sarcoidosis: A single-center retrospective cohort study - Boch, Katharina; Langan, Ewan A.; Zillikens, Detlef; Ludwig, Ralf J.; Kridin, Khalaf (Frontiers in Medicine, 2022)
Background: Cutaneous sarcoidosis is a relatively rare disease whose clinical manifestations include red-brown macules, plaques, papules and subcutaneous nodules. The skin changes may also be restricted to pre-existing scars. Approximately one third of patients with cutaneous sarcoidosis have systemic organ involvement. Objectives: Aim of this retrospective study was to longitudinally investigate clinical and laboratory findings in patients with cutaneous sarcoidosis. Methods: Patients (>18 years) with histologically confirmed cutaneous sarcoidosis between January 2014 and December 2020 were included. Patient demographics, clinical features, laboratory and radiological findings, management, clinical outcomes and co-morbidities associated with cutaneous sarcoidosis were analyzed. Results: Thirty-seven patients with cutaneous sarcoidosis were identified, of whom 56.8% were female. The most common clinical phenotype of specific cutaneous sarcoidosis was papular sarcoidosis (n=16), while plaques and nodules were present in 9 patients. In contrast, subcutaneous (n=1) and scar-associated sarcoidosis (n=1) were rare. Erythema nodosum was diagnosed in 10 patients. 62.2% of patients showed additional systemic involvement, with bilateral hilar lymphadenopathy being present in all 23 patients, of whom 4 patients fulfilled the diagnostic criteria for Löfgren syndrome. Levels of soluble interleukin (IL)-2 receptor, angiotensin converting enzyme (ACE), and C-reactive protein (CRP) were elevated, in 76.2%, 21.2%, and 50% of the tested patients respectively and predicted systemic involvement. Hypercalcemia was present in 5.6% of patients. Female sex and younger age (<54 years) were significantly associated with systemic manifestations Conlcusions: Cutaneous sarcoidosis was frequently associated with additional systemic involvement, particularly when present in young females.